Effect of blending GGBS and silica fume on the mechanical properties of geopolymer concrete - Mohammad Zuaiter; Ahmed Khalil; Mohamed Elkafrawy; Rami Hawileh; Mohammad AlHamaydeh; Ahmed Ayman; Tae-Yeon Kim (Scientific Reports)
Abstract This study investigates the mechanical properties of geopolymer concrete made with ground granulated blast furnace slag (GGBS) and silica fume (SF) as binders. The influence of varying binder proportions and sodium silicate-to-sodium hydroxide (SS-to-SH) ratios of 1.5 and 2.0 in the alkali-activated solution was examined. Experimental tests evaluated slump, compressive strength, modulus of elasticity, and splitting tensile strength at 1, 7, and 28 days. Increasing SF content up to 50% in the binder with a solution ratio of 1.5 improved the 28-day compressive strength by 50% compared to mixes made solely with slag. However, further increase in SF reduced splitting tensile strength and compressive strength by 79 and 56%, respectively, at 28 days. Increasing the solution ratio from 1.5 to 2.0 enhanced compressive strength for slag-dominant mixes by up to 63% but reduced strength for SF-rich mixes by up to 87%. The highest modulus of elasticity, 18.7 GPa, was achieved with slag-only binders and a solution ratio of 2.0, marking a 240% increase over its counterpart mix with a lower solution ratio. Equal GGBS and SF blends improved splitting tensile strength compared to SF-rich mixes but were surpassed by GGBS-rich mixes in terms of overall structural performance.